EFFECT OF DAHLIA TUBER INULIN EXTRACT ON FATTY LIVER IN TYPE 2 DIABETES MELLITUS RATS - Ismawati, Ismawati; Aufa, Athiatul; saryono, Saryono; Romus, Ilhami; Putri, Veni Dayu; Yanti, Sri; Dyna, Fitri (E-Jurnal Medika Udayana; Vol 13 No 9 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i09.P13, 2024)
Several studies show a correlation between intestinal microbiota disturbances and metabolic disorders, including type 2 diabetes mellitus (T2DM). Fatty liver is one of the complications that occurs due to T2DM. Fatty liver is characterized by the accumulation of lipids in the liver in response to increased triglyceride synthesis in hepatocytes and is thought to be associated with disturbances in the gut microbiota so that changes in the gut microbiota can be a potential target for T2DM treatment. It is known that inulin, a prebiotic, can improve intestinal microbiota disorders. This study aims to analyze the effect of administering inulin from dahlia tubers on fatty liver in T2DM rats.The research design is an experimental study with a post-test-only control group design conducted from June to November 2023. The study used twenty male Rattus norvegicus Wistar strain divided into five groups: a control group, a T2DM-induced group, T2DM groups given inulin extract at doses of 0.5 mg/gBW, 1.0 mg/gBW, and 1.5 mg/gBW. The results showed that the T2DM group had a higher significant percentage of fatty liver (p <0.01) than the control group. Compared to the T2DM group, there was a decrease in the percentage of fatty liver in the T2DM groups given inulin at all doses (p<0.05). This study concluded that inulin administration can reduce fatty liver in T2DM rats. Keywords : Dahlia tubers., fatty liver., inulin., type 2 diabetes mellitus